Are beavers a solution to the freshwater biodiversity crisis?. Issue 11 (22nd August 2019) - Law, Alan; Levanoni, Oded; Foster, Garth; Ecke, Frauke; Willby, Nigel J.
Abstract: Aim: To determine whether reintroduced beavers, as an example of native herbivorous megafauna, can increase freshwater biodiversity at the landscape scale and to compare effects on two contrasting taxonomic groups. Location: South‐central Sweden. Methods: We collected data on plant and water beetle composition and supporting environmental variables from 20 closely located wetlands, half created from the damming of streams by beavers—beaver ponds (BP), and half by other, mainly natural (e.g. topographic, river migration) means—other wetlands (OW). Differences in species composition and plant growth strategy (i.e. competitor, stress tolerator or ruderal) between wetland types were assessed using multivariate analyses. Results: The species pool of both taxonomic groups was higher in BP than OW (plants + 17%; beetles + 15%). For both groups, the number of species unique to BP was 50% higher than those unique to OW. Plant and beetle compositions differed significantly between wetlands, most strongly for plants, while rarity scores showed no difference, and the incidence of invasive species was negligible. Plant composition was mostly influenced by open water, bare ground and woody debris in BP, and plant cover, height and leaf litter in OW. This was consistent with the characterization of BP vegetation by ruderal plants and OW by competitors and stress tolerators. A significant residual effect of wetland type on plant, but not beetle composition, suggests that beavers exert important direct effects on some biota (e.g. via herbivory) independent of the indirect effects they exert via environmental change. Main conclusions: Beaver‐created ponds support novel biodiversity that is not merely a subset of that found elsewhere in the same landscape. As such, re‐establishing beaver populations where they are native should benefit freshwater biodiversity, but effects may be context and taxon specific. Beavers alone cannot solve the freshwater biodiversity crisis, but recognizing the widespread importance of herbivorous megafauna in maintaining heterogeneity and creating novel habitat will be a positive step.